Efficacy of dietary phytosome conjugated cinnamaldehyde supplementation on performance and economics in broilers: Performance and Economics of broilers - A.A. KONDHARE; M.M. KADAM; D.B. BHAISARE; S.V. CHOPADE; A.R. PATIL; G.K. NAGRE (Indian Journal of Poultry Science, 2025)
The present research was designed to assess the efficacy of dietary supplementation of phytosome conjugated cinnamaldehyde essential oil as a feed additive on growth performance and economics of broiler production. A total of 180 commercial broiler chicks (Vencobb-430) at one-day-old age were randomly divided into three groups of four replicates in each (60 chicks/group). The control group received the basal diet, while the other two groups received the basal diet supplemented with Bacitracin Methylene Disalicylate (BMD) @500gm per tonnes and phytosome conjugated cinnamaldehyde essential oil @ 100g/ton of feed, respectively for 42 days. The data obtained demonstrated that, in comparison to other groups, the group that received phytosome conjugated cinnamonaldehyde essential oil at a rate of 100 g/t of feed exhibited significantly (P